2017
DOI: 10.1016/s2214-109x(17)30220-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of mass drug administration in elimination of Plasmodium falciparum malaria: a consensus modelling study

Abstract: SummaryBackgroundMass drug administration for elimination of Plasmodium falciparum malaria is recommended by WHO in some settings. We used consensus modelling to understand how to optimise the effects of mass drug administration in areas with low malaria transmission.MethodsWe collaborated with researchers doing field trials to establish a standard intervention scenario and standard transmission setting, and we input these parameters into four previously published models. We then varied the number of rounds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(140 citation statements)
references
References 35 publications
(58 reference statements)
3
123
0
Order By: Relevance
“…The theoretically best timing of MDA campaigns relative to the malaria season peak have been investigated in (32). Critically, those models do not incorporate implementation logistics in a detailed manner, either simulating instantaneous MDA deployment in all villages, or having a synchronously increasing global coverage until a target coverage is reached.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretically best timing of MDA campaigns relative to the malaria season peak have been investigated in (32). Critically, those models do not incorporate implementation logistics in a detailed manner, either simulating instantaneous MDA deployment in all villages, or having a synchronously increasing global coverage until a target coverage is reached.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that MDA of praziquantel could certainly reduce egg positive prevalence of haematobium schistosomiasis. Although MDA is not an effective replacement for the existing vector control, MDA has the potential to reduce transmission for a limited time and has to be repeated regularly for sustained effect [38]. However, the egg positive prevalence in August 2013 was reduced from 3.8% to 0.9% two months after MDA (p=0.050).…”
Section: Discussionmentioning
confidence: 99%
“…In a consortium, several modelling groups develop their models independently, each applying their particular expertise and perspective. For example, consortia of malaria modellers were convened to predict the effectiveness of interventions, including a vaccine candidate 101 and mass drug administration 102 . Congruence of output among models engenders confidence that model results are robust.…”
Section: Pitfalls and How To Avoid Themmentioning
confidence: 99%